Clinical and digital subtraction angiographic (DSA) evaluation of patients of subarachnoid haemorrhage (SAH) in a tertiary level hospital (Bangladesh Medical Journal, 2016)
The present study was undertaken to evaluate the morphological anatomy of cerebral vessels in patients of aneurysmal subarachnoid hemorrhage. The cross-sectional observational study was carried out in the Department of Neurology, Dhaka Medical College Hospital, Dhaka from January 2013 to June 2013. Adult patients of spontaneous subarachnoid haemorrhage (SAH), diagnosed clinically and confirmed by CT scan of the head were included in the study. However, patients who are not capable financially of undergoing Digital Subtraction Angiography (DSA), traumatic subarachnoid haemorrhage, intracerebral haemorrhage and patients taking antiplatelet and anticoagulant drugs and with comorbidities were excluded. A total of 30 subjects meeting the above eligibility criteria were selected consecutively from the study population. The present study demonstrated that 80% of the patients were 50 or younger than 50 years old (mean age 45.0 ± 9.4 years) with a male preponderance (60%). Sudden headache accompanied by vomiting was invariably complained by the patients at onset of Athe disease. On admission two-thirds (66.7%) of the patients were unconscious. 4 out of 30(16.65%) patients exhibited neurological deficit. Of the risk factors, hypertension and smoking demonstrated their significant presence (around 45%) among the patients studied. Based on Glasgow Coma Scale, 7(23.3%) patients out of 30 in the present study were in grade-v. Our data showed that the common site of aneurysm was anterior communication artery (36.7%) followed by middle cerebral artery (26.7%) and posterior communicating artery (23.3%). Saccular aneurysms formed the main bulk (93%) of the cases irrespective of anatomical distribution of aneurysm. In aneurysmal subarachnoid haemorrhage, aneurysms are mainly located in anterior communicating and middle cerebral arteries and of medium-sized. Majority are saccular type and narrow-necked.Bangladesh Med J. 2015 Sep; 44 (3): 125-129